(7,5)(-4,-1)
slope = (-1-5) / (-4-7) = -6/-11 = 6/11
y - y1 = m(x - x1)
slope(m) = 6/11
(-4,-1)...x1 = -4 and y1 = -1
now we sub...pay close attention to ur signs
y - (-1) = 6/11(x - (-4) ...not done yet...
y + 1 = 6/11(x + 4) <===
Answer:
<em><u> </u></em><em><u>Given </u></em><em><u>:</u></em>
<em><u>=</u></em><em><u>></u></em><em><u> </u></em><em><u>An </u></em><em><u>equilateral</u></em><em><u> Triangle</u></em><em><u> </u></em><em><u>i.e </u></em><em><u>a </u></em><em><u>triangle</u></em><em><u> </u></em><em><u>which </u></em><em><u>have </u></em><em><u>all </u></em><em><u>it's</u></em><em><u> </u></em><em><u>side </u></em><em><u>equal.</u></em>
<em><u>To </u></em><em><u>Find </u></em><em><u>:</u></em>
<em><u>=</u></em><em><u>></u></em><em><u>The </u></em><em><u>value </u></em><em><u>of </u></em><em><u>(</u></em><em><u>2</u></em><em><u>x</u></em><em><u>)</u></em><em><u>°</u></em>
<em><u>-</u></em><em><u>-</u></em><em><u>-</u></em><em><u>-</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>_</u></em><em><u>-</u></em><em><u>-</u></em><em><u>-</u></em><em><u>-</u></em><em><u>❣️</u></em>
<h2>
<em><u>Solution</u></em><em><u> </u></em></h2>
<em><u>----_______----❣️</u></em>
<em><u>1</u></em><em><u>. </u></em><em>We </em><em>know</em><em> </em><em>that </em><em>the </em><em>sum </em><em>of </em><em>a </em><em>triangle</em><em> </em><em>is </em><em>1</em><em>8</em><em>0</em><em>°</em>
<em>2.We </em><em>also </em><em>know</em><em> </em><em>that </em><em>all </em><em>the </em><em>sides </em><em>of </em><em>a </em><em>triangle</em><em> </em><em>are </em><em>equal</em><em> </em><em>hence,</em><em> thier</em><em> </em><em>corresponding</em><em> </em><em>Angles </em><em>are </em><em>Equal</em><em> </em><em>too.</em>
<em>So.</em><em>.</em><em>.</em>
<em> </em><em><u>Each </u></em><em><u>angle </u></em><em><u>measures </u></em><em><u>6</u></em><em><u>0</u></em><em><u>°</u></em><em><u>. </u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em><em><u>(</u></em><em><u>.</u></em><em><u>1</u></em><em><u>)</u></em>
<em><u>3</u></em><em><u>.</u></em><em><u> </u></em><em>using(</em><em>1</em><em>)</em><em>,</em>
<em>We </em><em>can </em><em>find</em><em> the</em><em> </em><em>value</em><em> </em><em>of </em><em>x</em>
<h2>
<em>=</em><em>></em><em> </em><em>2</em><em>x</em><em>°</em><em> </em><em>=</em><em>6</em><em>0</em><em>°</em></h2><h2>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>x=</em><em> </em><em>6</em><em>0</em><em>/</em><em>2</em></h2><h2>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>x=</em><em> </em><em>3</em><em>0</em></h2>
Answer:1
V = 62.1262 cubic inches
Step-by-step explanation:
The formula for volume of a cone is V = (1/3)πr²h where r is the radius of the base, and h is the height.
We are given the height, h = 7 1/2 inches, or 15/2 inches
We are given the diameter of the base of 5 5/8 inches, or 45/8 inches
The radius is half the diameter, so divide 45/8 by 2. The radius is 45/16.
Plug these values into the formula and find V
V = (1/3)π(45/16)²(15/2)
V = 30,375π/1,536 = 62.12622191
rounding to 4 decimal places gives us 62.1262 cubic inches
Answer:
x=√2, x=-√2, x= 3 and x=-3
Step-by-step explanation:
We need to solve the equation x^4 - 11x^2+18=0
We can replace x^4 = u^2 and x^2 = u
So, the equation will become
u^2 -11u+18 = 0
Factorizing the above equation:
u^2 -9u-2u+18 =0
u(u-9)-2(u-9)=0
(u-2)(u-9)=0
u=2, u=9
As, u = x^2, Putting back the value:
x^2 =2 , x^2 =9
taking square roots:
√x^2 =√2 ,√x^2=√9
x=±√2 , x = ±3
so, x=√2, x=-√2, x= 3 and x=-3